2020
DOI: 10.3389/fphar.2020.00642
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms of Human Atherogenesis: Focus on Chronification of Inflammation and Mitochondrial Mutations

Abstract: Atherosclerosis is one of the most common diseases of the cardiovascular system that leads to the development of life-threatening conditions, such as heart attack and stroke. Arthrosclerosis affects various arteries in the human body, but is especially dangerous in the arteries alimenting heart and brain, aorta, and arteries of the lower limbs. By its pathophysiology, atherosclerosis is an inflammatory disease. During the pathological process, lesions of arterial intima in the form of focal thickening are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 83 publications
0
34
0
Order By: Relevance
“…64 Genetic variations with deletions and mutations in the mtDNA, but also in the nDNA, appear to influence the development of atherosclerosis and have been recognized as independent factors for disease emergence and may constitute potential diagnostic markers. 65,66 Interestingly, local differences of the mitochondrial genome have been suggested as a possible explanation of the mosaicism noted within the arterial tissue that leads to the focal localization of atherosclerotic lesions in the arterial wall, whereby some areas are more susceptible to development of atherosclerosis than others; these variations may turn out to be important for development of novel therapies. 65 A meta-analysis of 15 randomized controlled trials (RCTs) enrolling 5680 ST-elevation myocardial infarction (STEMI) patients having primary percutaneous coronary intervention (PCI) and comparatively evaluating drugs aimed at mitochondrial function versus placebo, indicated that drugs targeting a particular mitochondrial component/pathway did not lead to a significant decrease of CV and all-cause mortality (OR, 0.90 and OR, 0.92, respectively).…”
Section: Atherosclerosis/coronary Artery Disease (Cad)mentioning
confidence: 99%
See 2 more Smart Citations
“…64 Genetic variations with deletions and mutations in the mtDNA, but also in the nDNA, appear to influence the development of atherosclerosis and have been recognized as independent factors for disease emergence and may constitute potential diagnostic markers. 65,66 Interestingly, local differences of the mitochondrial genome have been suggested as a possible explanation of the mosaicism noted within the arterial tissue that leads to the focal localization of atherosclerotic lesions in the arterial wall, whereby some areas are more susceptible to development of atherosclerosis than others; these variations may turn out to be important for development of novel therapies. 65 A meta-analysis of 15 randomized controlled trials (RCTs) enrolling 5680 ST-elevation myocardial infarction (STEMI) patients having primary percutaneous coronary intervention (PCI) and comparatively evaluating drugs aimed at mitochondrial function versus placebo, indicated that drugs targeting a particular mitochondrial component/pathway did not lead to a significant decrease of CV and all-cause mortality (OR, 0.90 and OR, 0.92, respectively).…”
Section: Atherosclerosis/coronary Artery Disease (Cad)mentioning
confidence: 99%
“…Importantly, recent studies have indicated a number of mtDNA mutations, with the heteroplasmy level (proportion of normal and mutant mtDNAs present within the cell) linked to atherosclerosis, either positively or negatively, including early subclinical atherosclerotic disease; the mutations were detected in the genes that encode for the mitochondrial ribosomes, electron transport chain enzymes, and tRNA 64 . Genetic variations with deletions and mutations in the mtDNA, but also in the nDNA, appear to influence the development of atherosclerosis and have been recognized as independent factors for disease emergence and may constitute potential diagnostic markers 65,66 . Interestingly, local differences of the mitochondrial genome have been suggested as a possible explanation of the mosaicism noted within the arterial tissue that leads to the focal localization of atherosclerotic lesions in the arterial wall, whereby some areas are more susceptible to development of atherosclerosis than others; these variations may turn out to be important for development of novel therapies 65 …”
Section: Mitochondrial Dysfunction In Specific CV Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CVDs are heterogeneous in nature, they share some common pathological features, such as atherosclerosis and inflammation [ 37 , 38 ]. Recent studies have revealed that TFEB is critical to maintaining vascular and heart homeostasis ( Fig.…”
Section: Tfeb and Cvdsmentioning
confidence: 99%
“…Although the morbid etiopathogenesis is not entirely decipherable, atherosclerosis is known as a complex and chronic inflammatory disease [1,2]. Endothelial dysfunction occurs at the beginning of atherosclerosis and leads to hardening and thickening of the arterial wall and plaque formation [3].…”
Section: Introductionmentioning
confidence: 99%